Mysterious Wooden Objects Represented in the Punt Portico in the Temple of Hatshepsut at Deir el-Bahari - Taterka, Filip (Zeitschrift für ägyptische Sprache und Altertumskunde, 2021)
The article presents a previously unpublished block coming from the Southern Lower Portico (also known as the Punt Portico) in Hatshepsut’s temple of millions of years at Deir el-Bahari. It contains a depiction of a young Nubian man carrying two mysterious objects. The one is the double tjsw -staff, while the other is most likely a wooden stool. In order to support his identification of the objects in question, the author discusses some parallels coming from early 18 th dynasty private tombs at Thebes.